Differentiation of Shewanella putrefaciens and Shewanella alga on the basis of whole-cell protein profiles, ribotyping, phenotypic characterization, and 16S rRNA gene sequence analysis. - Vogel, B F (1997)
Seventy-six presumed Shewanella putrefaciens isolates from fish, oil drillings, and clinical specimens, the type strain of Shewanella putrefaciens (ATCC 8071), the type strain of Shewanella alga (IAM 14159), and the type strain of Shewanella hanedai (ATCC 33224) were compared by several typing methods. Numerical analysis of sodium dodecyl sulfate-polyacrylamide gel electrophoresis of whole-cell protein and ribotyping patterns showed that the strains were separated into two distinct clusters with 56% +/- 10% and 40% +/- 14% similarity for whole-cell protein profiling and ribotyping, respectively. One cluster consisted of 26 isolates with 52 to 55 mol% G + C and included 15 human isolates, mostly clinical specimens, 8 isolates from marine waters, and the type strain of S. alga. This homogeneous cluster of mesophilic, halotolerant strains was by all analyses identical to the recently defined species S. alga (U. Simidu et al., Int. J. Syst. Bacteriol, 40:331-336, 1990). Fifty-two typically psychrotolerant strains formed the other, more heterogeneous major cluster, with 43 to 47 mol% G + C. The type strain of S. putrefaciens was included in this group. The two groups were confirmed by 16S rRNA gene sequence analysis. It is concluded that the isolates must be considered two different species, S. alga and S. putrefaciens, and that most mesophilic isolates formerly identified as S. putrefaciens belong to S. alga. The ecological role and potential pathogenicity of S. alga can be evaluated only if the organism is correctly identified.